BIOM-54. A RAPID GENOTYPING PANEL FOR SENSITIVE AND SPECIFIC SEGREGATION OF CNS PATHOLOGIES. (9th November 2020) - Gupta, Mihir; Burns, Evan; Georgantas, Nicholas; Thierauf, Julia; Nayyar, Naema; Burns, Ryan; Velarde, Jose; Brastianos, Priscilla; Dietrich, Jorg; Marble, Hetal; Lennerz, Jochen; Romero, Javier; et al.
Abstract: Primary central nervous system lymphoma (PCNSL) remains challenging to diagnose due to nonspecific clinical and radiologic features and low diagnostic yields of cerebrospinal fluid (CSF) studies. We sought to characterize the diagnostic approach of suspected PCNSL, in order to improve clinical workflow. We first reviewed 1, 007 new brain lesions of unknown etiology that included PCNSL in the radiologic differential diagnosis. The most common final diagnoses included high-grade glioma (28.2%) and PCNSL (14.6%). Diagnostic biopsies were frequently performed for high-grade glioma (100%) and PCNSL (94.4%), while CSF was frequently sampled for PCNSL (78.7%). We next identified 159 patients with an established new diagnosis of PCNSL. CSF studies were non-diagnostic in 86.7% of cases, whereas biopsy was positive in 93%. However, intraoperative histopathology was inconclusive for PNCSL in 54.5%, likely contributing to 22% of patients undergoing surgical resection. These challenges resulted in 12 days median time to treatment initiation, and readmission for further workup or treatment initiation in 27% of patients. These results indicated the need for a rapid, sensitive and specific platform to segregate PCNSL and glioma using CSF and tissue samples. We developed a qPCR-based assay to genotype the MYD88 L265P hotspot mutation from CSF and plasma within 80 minutes of sample acquisition. Results were concordant with orthogonal DNA sequencing in extracts from 87 archived specimens, with detection limits of 490pg of input genomic DNA and 0.15% mutant allele frequency. When performed simultaneously with assays for TERT promoter, IDH1/2, H3F3A and BRAF point mutations, the resulting panel accurately segregated PCNSL and adult diffuse glioma molecular diagnoses in 87 archived specimens and 19 prospective liquid biopsies, including cases of lymphoma and glioma. We propose that inclusion of targeted analysis of these mutually exclusive recurrent molecular alterations characterizing gliomas and PCNSL will facilitate rapid, sensitive diagnosis from solid and liquid biopsies.